Susceptibility of blackfly larvae to the larvicide Temephos in Caarapó, MS - Teixeira, Tatiane Zaratini; Arruda, Eduardo José; Fernandes, Magda Freitas; Andrade, Carlos Fernando Salgueirosa; Crispim, Bruno do Amaral; Nakamura, André Kioshi da Silva; Silva, Emerson Pereira da (BioAssay, 2014)
Blackfly control in Brazil is necessary to avoid nuisance to rural or urban communities and economic losses in agricultural or tourist activity areas. The susceptibility of Simulium spp. larvae was performed to the organophosphate temephos (Abate 500 CE) at the Caarapó stream, in the city of Caarapó in the state of Mato Grosso do Sul. The resistance to the larvicide was indicated by the rapid biochemical test of esterase activity carried out with extracts of larvae, and confirmed by the results of the field bioassay with larvae in troughs in the stream bed. For the field bioassay final stage larvae were exposed to a Temephos Operational Concentration of 0.5 ppm ai/10 minutes and a Diagnostic Concentration of 2.5 ppm ai/10 minutes and low mean mortality was obtained (5.7% and 44.6 % respectively), confirming the resistance and indicating the need for using other products for blackfly control in this area.